Transformasi Keuangan dan Perpajakan Digital bagi Poklahsar Desa Klampis Barat - Yani, Prawita; Susila, Muktar Redy; Nugroho, Wawan Cahyo; Pradhani, Fastha Aulia; Zuhroh, Nur Fatimatuz (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Global mobilization has become the main motivation for digital transformation in Small Medium Enterprises (SME). Financial statement from digital recording will provide the inclusive access for government and private funding as well. This community development implemented with joint partnership from Kelompok Pengolah dan Pemasar (Poklahsar) of Klampis Barat village in Bangkalan District. The target itself is mastering friendly-user digital accounting and tax app. So far SMEs under Poklahsar have difficulties to prepare a complete and real-time financial statement, so it can be crucial for business development. As for SME accounting app, it should be easy to understand, implement and analyze, therefore the method was to held socialization first then followed by MoneyLover training and mentoring. Lastly, monitoring and evaluation was held to ensure the implementation by assigning financial recording from last month. The implication would make financial and tax recording by MoneyLover as digital transformation for SMEs in Klampis Barat.